Alternative oak in the maturation of wines Cabernet Sauvignon - T. B. Hamm; R. A. G. Kohn; E. P. Pinto; L. Lucchetta; V. Manfroi; C. V. Rombaldi (Scientific Electronic Archives, 2014)
The wine maturation with classic oak is a practice used for a long time, but recently the alternative means (fragments) has been used for its lower cost and practicality. In this study, the alternative wooden barrel was evaluated sit tested two types of oak fragment (chip and cube) and two doses (1 and 2 g L-1). The variables analyzed were as physicochemical characteristics and sensory analysis. The wines showed positive characteristics in general quality, highlighting the conditions of body / frame and wood notes. However, the dosage interfered significantly in the general quality. The "chip" alternative oak, dosage of 2 g L-1 resulted in excessive wood notes, vegetable odor undesirable, which had a negative influence on the general quality of the wine. The two types of fragments (chip and cube) are effective in the maturation of red wines. Although, the types of fragments are conditioned to the doses employed.